Was there really a siege of Kaffa by the Mongols in 1346 the first biological war? And what was the aftermath? - Christensen Carsten Sander (Studia Humanitatis)
On the basis of the 14th century manuscript by the Genoese Gabriele de’ Mussi many historians widely believe that plague called the Black Death had to have reached European continent from the port city of Kaffa (modern-day Theodosia) on the Crimea peninsula as a result of a biological warfare by the Mongols. This is not only a historical interest but also relevant to current efforts to evaluate the threat of military or terrorist use of biological weapons. Based on published translations of the de’ Mussi’s manuscript and other 14th-century accounts of the Black Death it can be concluded that the Mongol attack was a biological warfare at Kaffa and provides the best explanation of the plague entry into the city. However, questions arise. Even though such a theory is consistent with the technology of those times and in a way with contemporary notions about the dangers and necessary caution in the treatment of such diseases, the report has a number of weaknesses in terms of practical implementation. This paper sheds light on the dark points of Gabriele de’ Mussi’s manuscript of the siege of Kaffa in the year 1346.